Analisis Metafora dalam Pantun Pernikahan Melayu Kepulauan Riau (Natuna) melalui Pendekatan Stilistika Gorys Keraf - Hilda Enonia Gea; Sri Rahayu; Anggeli Anggeli; Desi Putri Amelia; Laras Andina; Nofanda Dwi Anggraini; Nur Ifni Hayati; Syalsha Desta Auliya (Kampus Akademik Publiser, 2026)
Wedding pantun is part of the oral tradition of the Malay community of the Riau Archipelago, particularly in Natuna, which contains cultural values and linguistic aesthetics. This study aims to describe the forms and types of metaphor and to analyze the figurative meanings of metaphor in Malay wedding pantun of the Riau Archipelago (Natuna) based on the theory of Gorys Keraf (1991). This qualitative descriptive research uses six pantun as data, obtained through interviews. The results show that not all pantun contain metaphors; only three out of six data exhibit the use of live metaphors. These metaphors function to convey symbolic meanings of beauty, respect, and humility before God. All metaphors found are classified as live metaphors, reflecting the cultural, social, and religious values of the Malay community.